Reconstruction of remote climate change from borehole temperature measurement in the eastern part of Morocco. - Barkaoui, A. (2013)
Data from temperature measurements inboreholes are indicators of the temperature variations associated with past climate change. This paper is a contribution to reconstruct the ground surface temperature history (GSTH) from geothermal data in the eastern part of Morocco. From a set of several temperature logs, measured in the study area, only two were found suitable for estimating the ground surface temperature history (GSTH). In order to reconstruct the surface temperature past changes the functional space inversion method (FSI) was used. The inversion reveals a recent warming in the last century with respective amplitude of 0.1 °C and 1 °C for the boreholes 2952 in Oujda and 1624 in Berkane. These results can be confirmed by the air temperature record of the meteorical station in Oujda despite the scarceness of data beyond 1959.